Exploratory analysis for the optimization of culture media for bacillus thuringiensis fermentation (2004)
Agrichemical involve health risks for producers and consumers; they can also affect beneficial insects, birds, fish and mammals. Bacillus thuringiensis-based biopesticides specific for insect plagues are available, which, represent an alternative to traditional chemically-based products. Culture media design is an impor-tant factor in the production of biopesticides based on Bacillus thuringiensis. The media have to be economi-cal and they must contain all the nutrition factors required by the bacteria. The yield of active ingredient, comprising the toxin-containing crystal protein and bacterial spores, must be high and with adequate toxi-city to formulate the biopesticide. In this work we studied different culture media and optimised a promi-sing culture medium for B. thuringiensis fermentation to obtain an active ingredient for use as raw material in manufacturing a biopesticide. The final concentration of active ingredient was 15 to 16 g/L and the raw material cost around US $0,30/kg product. Calculations for the experimental phase were done using the response surface technique in a central composite design (CCD), the optimisation phase used Derringer and Suich (1980) method for dual response. Key words: Biopesticides, culture media, surface response, dual response, contour plots, central composite design.